2019
DOI: 10.18393/ejss.468100
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and clinoptilolite zeolite on selected chemical properties of soil cultivated with maize (Zea mays L.)

Abstract: Increase in cost of chemical fertilizers encourages the use of soil amendments such as biochar and zeolites to improve soil fertility. In this study, biochar produced from empty fruit bunch-palm oil mill effluent (EFB-POME) and clinoptilolite zeolite were used as soil amendments to improve soil fertility. The field experiment was carried out for two planting cycles to determine the effects of different rates of EFB POME biochar (0, 10, and 20 t ha-1), clinoptilolite zeolite (0, 1.25, and 2.5 t ha-1), and urea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
(43 reference statements)
1
20
0
1
Order By: Relevance
“…We believe this increased K concentration in the soil resulted from the applied K with the biochar's ash. Many researchers have also reported similar results [32,58,59]. For instance, in tropical acid soil, soil exchangeable K increased using 5 t ha −1 chicken litter biochar [60].…”
Section: Biochar and Lime Treatment Affects Soil Propertiesmentioning
confidence: 59%
See 1 more Smart Citation
“…We believe this increased K concentration in the soil resulted from the applied K with the biochar's ash. Many researchers have also reported similar results [32,58,59]. For instance, in tropical acid soil, soil exchangeable K increased using 5 t ha −1 chicken litter biochar [60].…”
Section: Biochar and Lime Treatment Affects Soil Propertiesmentioning
confidence: 59%
“…Globally, maize is one of the leading cereal crops, providing food and feed for humans and animals, along with diverse raw materials for agricultural industries [32]. Many different foods and feed items are prepared from maize, providing multiple nutrients and vitamins [33].…”
Section: Introductionmentioning
confidence: 99%
“…By applying 10 and 20 t ha -1 biochar, soil exchangeable K increased from 64.30% to 111.57%, respectively, compared with the control soil. The control soil without biochar exhibited the lowest soil exchangeable K, approximately 10.98 mg kg -1 (Zaidun et al, 2019). In soil treated with urea and 20 and 40 t ha -1 biochar, Zhang et al (2011) indicated increased SOC from 25% to 42%, respectively, compared with the control.…”
Section: Aluminum Toxicity and Nutrient Availabilitymentioning
confidence: 88%
“…Maize (Zea mays L.) is one of the leading cereal crops in the tropics, providing a source of food and oil for human beings and feed for animals along with diverse raw materials for agro-based industries (Zaidun et al, 2019). It is a vital crop worldwide and can grow in different types of soil and in a wide range of climates (Agegnehu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After 30 days of leaching, the soil CECs of the CLB (SB1, SB2, SB3, and SB4) were significantly higher compared to that of SK (Figure 4). The increased CEC of the tropical peat soil with CLB was due to an increase in the net charges of the biochar surface, which are able to attract more cations [43]. The slow oxidation of biochar increased the number of carboxylic, phenolic, alcoholic, and functional groups, resulting in an increase in the CEC of the soil with CLB [44].…”
Section: Clinoptilolite Zeolite Forest Litter Compost and Chicken Litter Biochar On Cation Exchange Capacity Of Peat Soil After Thirty Damentioning
confidence: 99%